Dampak Sosial Ekonomi Akibat Keberadaan Kegiatan Usaha Ternak Ayam Ras Pedaging (Studi Kasus Desa Serdang Kecamatan Tanjung Bintang Kabupaten Lampung Selatan) - Wintari Mandala; Novia Ambar Sari; Diah Reni Asih (Program Studi Agribisnis Universitas Sumatera Selatan, 2023)
Broiler chicken farming activities carried out by some livestock business actors clearly have positive and negative impacts. The aim of this research is to find out how the community responds to the existence of broiler chicken farming and to find out the socio-economic impact on communities adjacent to the farm. The samples in this study were residents of Serdang village and owners of broiler chicken farming businesses. The key informants used as samples were determined deliberately (purposive sampling). This research was conducted using qualitative methods. The results of the research show that people who live close to farms do not mind the existence of broiler farming activities as long as they do not cause excessive negative impacts. The positive social impact on local residents of livestock activities can provide motivation and the community's desire to raise livestock. broiler chickens. The proximity of farms to residential areas makes people feel they are benefiting because it makes it easier for people to buy chicken meat at a cheaper price. The negative impact of livestock farming will cause environmental pollution, conflict and competition. The economic impact has a positive impact in the form of additional income from offering and selling broiler chickens from farms to consumers outside the village. There needs to be efforts to monitor and control the environment appropriately in order to reduce environmental pollution for sustainable agriculture.